“Efecto residual del encalado, en segunda campaña, en el rendimiento del cultivo de soya (glycine max), variedad cristalina en un suelo ultisol en el bajo mayo” - Torres Trigozo, Groder (2005)
Thé present work was driven in the experimental field of the 1 Found Aucaloma of the UNSM, county of you Lick, region San Martin (Peru), located geographically at 6º 29 ' South Latitude and 76º 21 ' Longitude West toan altitude of 650 m.s.n.m The present experiment had as objective to evaluate the residual effect of 9 dose of amendment calcium magnésica" Magnecal ", on the behavior and· yield of the cultivation of Soya, Crystalline variety, likewise the dose was determined of having whitewashed technical and economically appropriate for the farmers seated in degraded sour floors. The design statistical employee was the Block Completely Randomizado (BCR) with 4 blocks and 9 treatments~ For the s.t atistical analysis and to check the observed variables, the variance Analysis was used (ANVA) and the test of Duncan to 0.05% of piobability. The characteristics of the floor were of texture Frank Sand, of sour reaction (pH 5.72), half content of organic matter of 3.15%, with readiness of m~tch of 11 ppm, contained first floor of interchangeable cationes and saturation of aluminum of 37.5%, relatively high; The evaluated treatments were O.O, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5 and 4.0 Tm/Ha. of Magnecal, of which you concludes that it existed highly significant differences for the factor of dose of Magnecal, for _ yv~_élt was increased the grain yields, with the biggest doses, having stood out the treatments T7 with · 1447.00 Kg/Ha, T8 with 1467.00 Kg/Ha and T9 with 1651.00 Kg/Ha. That in turn allowed to obtain the best economic benefits for hectare, with a net value of the production of SI. T4 SI. 313.26, T5 SI. 394.67, T6 SI. 619.41, T7 SI. 798.45, T8 SI. 828.92 y T9 SI. 1104.96 new suns respectively, representing only the monetization of the farmer's work, to have minimum margins of gain.